Control System for Nutrient Solution of Nutrient Film Technique Using Fuzzy Logic - Muhammad Naufal Rauf Ibrahim; Mohamad Solahudin; Slamet Widodo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Nutrient Film Technique (NFT) is one of the hydroponic systems, which the nutrient is circulated through root of the plants. Electrical conductivity (EC) of nutrient solution on hydroponic culture is a crucial point that determines the growth rate of the plants and quality of the products. The purpose of this research is to design the control system for nutrient solution to maintain the EC of nutrient solution using Arduino. Fuzzy logic control system was used with EC error and volume of nutrient solution as inputs. Model of tomato cultivation based on certain reference was simulated with scale 1:1440 for cultivation time. This model was used as disturbance of nutrient solution EC due nutrient uptake. The result of observation showed that system could reach setpoint after 130 seconds when the setpoint changes from 1.7 mS/cm to 1.6 mS/cm and 207 seconds from 1.6 mS/cm to 1.9 mS/cm. During observation, RSME value of the system while steady state was 0.005 mS/cm.